Draft Annual Plan Rajasthan 1980-81 - Planning Commission (Planning Commission, 1980)
With the termination of Fifth Five Year Plan one year ahead of schedule, 1978-79 took use shape of the first year of the Sixth The Planning Commission has approved a total 175' crores for Rajasthan for the mid land 1978-83. In the first year i.e. 1970-79, expenditure of Rs. 256.75 crores was incurred, For the year 1979-80, Planning Commission Subsequently has approved a plan outlay of Rs. 275 crores.
Planning Department Government of Rajasthan
Planning Department Government of Rajasthan